# |
ODE |
Mathematica |
Maple |
\[
{}\ln \left (y^{\prime }\right )+x y^{\prime }+a y+b = 0
\] |
✓ |
✓ |
|
\[
{}\ln \left (y^{\prime }\right )+a \left (x y^{\prime }-y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y \ln \left (y^{\prime }\right )+y^{\prime }-y \ln \left (y\right )-x y = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (y^{\prime }\right )+y^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}a \cos \left (y^{\prime }\right )+b y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} \sin \left (y^{\prime }\right )-y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+{y^{\prime }}^{2}\right ) \sin \left (x y^{\prime }-y\right )^{2}-1 = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+{y^{\prime }}^{2}\right ) \left (\arctan \left (y^{\prime }\right )+a x \right )+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}a \,x^{n} f \left (y^{\prime }\right )+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right )^{n} f \left (y^{\prime }\right )+y g \left (y^{\prime }\right )+x h \left (y^{\prime }\right ) = 0
\] |
✗ |
✗ |
|
\[
{}f \left (x {y^{\prime }}^{2}\right )+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}f \left (x -\frac {3 {y^{\prime }}^{2}}{2}\right )+{y^{\prime }}^{3}-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } f \left (x y y^{\prime }-y^{2}\right )-x^{2} y^{\prime }+x y = 0
\] |
✗ |
✗ |
|
\[
{}\phi \left (f \left (x , y, y^{\prime }\right ), g \left (x , y, y^{\prime }\right )\right ) = 0
\] |
✗ |
✗ |
|
\[
{}{y^{\prime }}^{2}+\left (x +y\right ) y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+y^{2} = 1
\] |
✓ |
✓ |
|
\[
{}\left (2 x y^{\prime }-y\right )^{2} = 8 x^{3}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) {y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-\left (y^{2}+2 x \right ) {y^{\prime }}^{2}+\left (x^{2}-y^{2}+2 x y^{2}\right ) y^{\prime }-y^{2} \left (x^{2}-y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }-y+\ln \left (y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}4 x {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}y = -x y^{\prime }+x^{4} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x +y^{\prime } y \left (2 {y^{\prime }}^{2}+3\right ) = 0
\] |
✗ |
✓ |
|
\[
{}a^{2} y {y^{\prime }}^{2}-2 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-4 x y y^{\prime }+8 y^{2} = 0
\] |
✗ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right )^{2} = 1+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}4 \,{\mathrm e}^{2 y} {y^{\prime }}^{2}+2 x y^{\prime }-1 = 0
\] |
✓ |
✓ |
|
\[
{}4 \,{\mathrm e}^{2 y} {y^{\prime }}^{2}+2 \,{\mathrm e}^{2 x} y^{\prime }-{\mathrm e}^{2 x} = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{2 y} {y^{\prime }}^{3}+\left ({\mathrm e}^{2 x}+{\mathrm e}^{3 x}\right ) y^{\prime }-{\mathrm e}^{3 x} = 0
\] |
✗ |
✓ |
|
\[
{}x y^{2} {y^{\prime }}^{2}-y^{3} y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) \left (1+y^{\prime }\right )^{2}-2 \left (x +y\right ) \left (1+y^{\prime }\right ) \left (x +y y^{\prime }\right )+\left (x +y y^{\prime }\right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y = 2 x y^{\prime }+y^{2} {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}a^{2} y {y^{\prime }}^{2}-2 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -y^{\prime }-y\right )^{2} = x^{2} \left (2 x y-x^{2} y^{\prime }\right )
\] |
✗ |
✗ |
|
\[
{}y^{2} \left (1+{y^{\prime }}^{2}\right ) = a^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = \left (x -b \right ) {y^{\prime }}^{2}+a
\] |
✓ |
✓ |
|
\[
{}x^{3} {y^{\prime }}^{2}+x^{2} y y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}3 x {y^{\prime }}^{2}-6 y y^{\prime }+x +2 y = 0
\] |
✓ |
✓ |
|
\[
{}y = \left (1+x \right ) {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right ) \left (x +y y^{\prime }\right ) = a^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+2 y y^{\prime } \cot \left (x \right ) = y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2}-1 = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-2 \left (x y+2 y^{\prime }\right ) y^{\prime }+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\frac {y {y^{\prime }}^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2} = x^{2} y^{2}+x^{4}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\frac {1}{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-2 \left (x y-2\right ) y^{\prime }+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-\left (x -1\right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}8 \left (1+y^{\prime }\right )^{3} = 27 \left (x +y\right ) \left (1-y^{\prime }\right )^{3}
\] |
✓ |
✓ |
|
\[
{}4 {y^{\prime }}^{2} = 9 x
\] |
✓ |
✓ |
|
\[
{}y \left (3-4 y\right )^{2} {y^{\prime }}^{2} = 4-4 y
\] |
✓ |
✓ |
|
\[
{}{x^{\prime }}^{2}+t x = \sqrt {t +1}
\] |
✗ |
✗ |
|
\[
{}{y^{\prime }}^{2}-4 y = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}-\left (x^{2}+y^{2}\right ) y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = 9 y^{4}
\] |
✓ |
✓ |
|
\[
{}x^{2}+{y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}x = {y^{\prime }}^{3}-y^{\prime }+2
\] |
✗ |
✓ |
|
\[
{}y = {y^{\prime }}^{4}-{y^{\prime }}^{3}-2
\] |
✗ |
✓ |
|
\[
{}{y^{\prime }}^{2}+y^{2} = 4
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-{\mathrm e}^{2 x} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y = 5 x y^{\prime }-{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = x^{2}+2 x y^{\prime }+\frac {{y^{\prime }}^{2}}{2}
\] |
✗ |
✓ |
|
\[
{}y \left (1+{y^{\prime }}^{2}\right ) = a
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+\left (x +a \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-2 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+2 y y^{\prime } \cot \left (x \right )-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\sinh \left (x \right ) {y^{\prime }}^{2}+3 y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} \sqrt {y} = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+x y {y^{\prime }}^{2} = \ln \left (x \right )
\] |
✗ |
✗ |
|
\[
{}{y^{\prime }}^{2}-y^{\prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x y \left (1-{y^{\prime }}^{2}\right ) = \left (-y^{2}-a^{2}+x^{2}\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y+\frac {x}{y^{\prime }} = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y = 2 x y^{\prime }+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = x {y^{\prime }}^{2}+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = \left (1+y^{\prime }\right ) x +{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = y {y^{\prime }}^{2}+2 x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y = y y^{\prime }+y^{\prime }-{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\sqrt {1-{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\frac {1}{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }-\frac {1}{{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y = x {y^{\prime }}^{2}+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-4 y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-9 x y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = x^{6}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }-{y^{\prime }}^{3} = y
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }-y-2 \left (t y^{\prime }-y\right )^{2} = y^{\prime }+1
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }-y-1 = {y^{\prime }}^{2}-y^{\prime }
\] |
✓ |
✓ |
|
\[
{}1+y-t y^{\prime } = \ln \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}1-2 t y^{\prime }+2 y = \frac {1}{{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y = -t y^{\prime }+\frac {{y^{\prime }}^{5}}{5}
\] |
✓ |
✓ |
|
\[
{}y = {y^{\prime }}^{2} t +3 {y^{\prime }}^{2}-2 {y^{\prime }}^{3}
\] |
✓ |
✓ |
|